2016
DOI: 10.1111/jgs.14077
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prevalence and Determinants of Potentially Inappropriate Prescribing in the United States: 2007 to 2012

Abstract: Objectives To estimate prevalence and determinants of potentially inappropriate prescribing (PIP) among US older adults using 2012 Beers criteria. Design Retrospective cohort study in a random national sample of Medicare beneficiaries. Setting 2007–2012 fee-for-service Medicare beneficiaries. Participants US population aged >65 years with Part A, B and D enrollment in at least 1 month during a calendar year (N=38,250 patients; 1,308,116 observations) Measurement We used 2012 Beers criteria to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
106
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 22 publications
8
106
1
Order By: Relevance
“…A recent study from Canada also reported that increasing age had a slightly greater protective effect among women than men . The finding of the higher risk of PIMs among women is in concordance with previous studies . A potential explanation for this result may be more frequent healthcare service use among women …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A recent study from Canada also reported that increasing age had a slightly greater protective effect among women than men . The finding of the higher risk of PIMs among women is in concordance with previous studies . A potential explanation for this result may be more frequent healthcare service use among women …”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study also showed that there were regional differences in PIM initiation between hospital districts. Previous studies provide mixed findings related to regional differences with PIM use . For example, studies have reported lower rates of PIMs in smaller hospitals or rural areas and regions in smaller populations .…”
Section: Discussionmentioning
confidence: 98%
“…A recent large cohort study of US Medicare beneficiaries found that the strongest predictor of PIM use among the factors studied was the number of drugs dispensed. 23 Similarly, multiple studies have consistently revealed that taking more prescription medications increases the risk of exposure to a PIM. 24,25 The number of prescription medications, as well as the number of PIMs themselves, could be a reasonable red flag that warrants deprescribing for older multimorbid patients in FMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Psycholeptics also represent an important and common type of potentially inappropriate medication class prescribed, especially diazepam. Turning to potentially inappropriate medication use prevalence, the data presented in our study are consistent with the findings of previous studies . This study reveals a high potentially inappropriate medication use prevalence both on admission (ranging from 69.9% to 72.6%) and discharge times (ranging from 67.6% to 73.5%), with a good agreement between the 2 lists of criteria.…”
Section: Discussionmentioning
confidence: 98%